2020
DOI: 10.1111/bjhp.12485
|View full text |Cite
|
Sign up to set email alerts
|

Resilience during uncertainty? Greater social connectedness during COVID‐19 lockdown is associated with reduced distress and fatigue

Abstract: Background. Social connections are crucial for our health and well-being. This is especially true during times of high uncertainty and distress, such as during the COVID-19 lockdown. This period was characterized by unprecedented physical distancing (often communicated as social distancing) measures resulting in significant changes to people's usual social lives. Given the potential effects of this disruption on people's well-being, it is crucial to identify factors which are associated with negative health ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
196
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(219 citation statements)
references
References 57 publications
20
196
1
2
Order By: Relevance
“…Correlational results indicated that coronavirus stress had a significant relationship with optimism, social connectedness, and COVID-19 burnout. These results are consistent with earlier research that reported relationship between coronavirus stress and COVID-19 burnout (Talaee et al, 2020;Yıldırım & Solmaz, 2020), coronavirus stress and optimism (Arslan et al, 2020;, coronavirus stress and social connectedness (Nitschke et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Correlational results indicated that coronavirus stress had a significant relationship with optimism, social connectedness, and COVID-19 burnout. These results are consistent with earlier research that reported relationship between coronavirus stress and COVID-19 burnout (Talaee et al, 2020;Yıldırım & Solmaz, 2020), coronavirus stress and optimism (Arslan et al, 2020;, coronavirus stress and social connectedness (Nitschke et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…The role of social connectedness in protecting mental health occurred in various health crises including COVID-19 pandemic (Liotta et al, 2020). A high level of social connectedness during COVID-19 pandemic was related with reduced distress and fatigue (Nitschke et al, 2020). Therefore, social connectedness can play a protective or mitigative factor during a crisis impacting mental health of healthcare staffs.…”
Section: Optimism and Social Connectedness As Mediatormentioning
confidence: 99%
“…A positive outlook towards life helps one to combat the negative effects of stress (Taylor et al, 2010). Resilience is the ability to bounce back post adversity, and this EI dimension was found to help cope with the challenges created by the pandemic situations (Nitschke et al, 2020).…”
Section: Study Findings and Discussionmentioning
confidence: 99%
“…On the other hand, social connectedness is essential to reduce social isolation and loneliness for older individuals (Cornwell et al, 2008;O'Rourke et al, 2018). Besides, social connectedness can protect individuals from stress-related consequences such as post-traumatic stress, blood pressure, and fatigue (Kintzle et al, 2018;Nitschke et al, 2020;Ong & Allaire, 2005).…”
Section: The Role Of Social Connectedness Between Social Support and mentioning
confidence: 99%
“…Although some studies investigating social connectedness or the changes of social connectedness during the pandemic (Folk et al, 2020;Nitschke et al, 2020), these studies only used data in limited numbers of countries. Thus, the findings might have limitations to be generalized to other cultural groups.…”
Section: The Present Studymentioning
confidence: 99%